THE EFFECT OF AIR TEMPERATURE AND DURATION OF SOLAR ILLUMINATION ON ANTHOCYANIN ACCUMULATION IN CHERRY PLUM FRUITS WITH VARIOUS MATURATION PERIODS - O. A. Grebennikova; A. A. Richter; V. M. Gorina (Труды по прикладной ботанике, генетике и селекции, 2018)
The article presents the data of a long-term research on the effect of air temperature and sunshine duration on the increase in anthocyanin content in the fruits of cherry plum varieties with different maturation periods and on their coloration degree. It is shown that the duration of sunshine is inversely associated with anthocyanin accumulation, which indicates the possibility of biosynthesis of these pigments under reduced illumination. Correlations between the accumulation of anthocyanins and daytime, night, and total air temperatures were absent.